Study on mechanical and magnetic properties of Cu/Ni multilayer composite fabricated by accumulative roll bonding process. (1st August 2013) - Eslami, A H; Zebarjad, S Mojtaba; Moshksar, M M
<x xml:space="preserve">Abstract</x> Accumulative roll bonding (ARB) has been used as a severe plastic deformation process for the production of high strength materials. In the current research, multilayered copper/nickel composites were produced by the ARB process using nickel and copper strips. Tensile and magnetic behaviours of produced composites were investigated by universal tensile machine and magnetic device detector (vibrating sample magnetometers) respectively. It was observed that as passes of ARB proceeded, nickel layers were necked and fractured gradually. After five roll bonding passes, a multilayer copper/nickel composite including homogeneously distributed fragmented nickel layers in the copper matrix was achieved. Magnetic and mechanical properties of these composites were studied within different stages of the ARB process. With increasing strain during ARB passes, strength, microhardness and elongation of these composites increased. Enhancement of the strength is higher than the tensile strength of copper/copper multilayered strips produced by the ARB process. In addition, it has been found that the magnetic properties, e.g. retentivity, coercivity and magnetic saturation of the multilayer composite, were significantly influenced by the changes in microstructural and grain size.